Transformasi Marginal dalam Pemberdayaan Komunitas Nelayan melalui Program Pembudidayaan Ikan Air Tawar - Tifa Maylasandi (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2025)
This research analyzes the transformation of the fishing community in Nagari Ampang Pulai, Koto XI Tarusan District, which is classified as a marginal community. These communities face challenges in accessing economic, educational, and health resources that hinder their social functioning.  The empowerment program through a top-down process which is considered effective actually kills the creativity of the people of this area. The marginal concept in the fishing community in Nagari Ampang Pulai is reviewed in several empowerment perspectives. First, the functional perspective reveals how social structure and economic function in the face of social inequality and external change. Second, the conflict perspective reveals structural injustice and economic exploitation by elite groups that exacerbate poverty. Third, a critical approach highlights social policies and programs. Fourth, the symbolic interactionalist perspective highlights how meaning and expectations constructed through daily interactions reinforce feelings of powerlessness and injustice. This research focuses on how people who work as fishermen manage their income, explaining how cultural concepts influence interaction patterns, as well as empowerment efforts made by the government to improve the economy for fishing communities. Through marginalization studies, this research uses qualitative methodology with a phenomenological research approach. Data was collected using observation, documentation and interview techniques. The research results show that the fishing community is avoidant in managing finances, there is domination of social differentiation which influences the social structure in society in Nagari Ampang Pulai, and empowerment programs for the fishing community.